METODE JIGSAW LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 11 SMA NEGERI 1 PAJAR BULAN - Elvy At Taroh; Imron Rosyadi; Indah Wigati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2023)
This study aims to improve the process quality and learning abilities of class XI IPS 2 students in PAI subjects at Pajar Bulan State High School for the 2022/2023 academic year by using the jigsaw cooperative learning method through Audio Visual PowerPoint media. This research is a class action research (CAR). Data collection was carried out using observation sheets and practice tests which were carried out at the end of each cycle which consisted of planning, implementing, observing, and reflecting. The subjects of this study were 15 students in class XI IPS 2 of SMA Negeri Pajar Bulan, consisting of 10 boys and 5 girls. In the use of the method cooperative learning jigsaw model through Audio Visual powerpoint media, can improve student learning outcomes per cycle. Cycle I the average value of students was 76 and increased in cycle II to 82.67. Mastery learning outcomes in cycle 1 of 73.33% increased to 93.33% in learning activities in cycle II. From the results of this study it can be recommended that the use of the jigsaw cooperative learning method through Audio Visual powerpoint media, can be applied by teachers in PAI learning in schools to improve student learning outcomes.